Clareamento dental caseiro: microbiota, sensibilidade dental e eficácia - Hamada, Érica Luriko (2019)
Tooth bleaching has become a very requested aesthetic procedure in the looking-for a perfect smile. It is an easy and conservative technique, with fast and satisfactory results and a great media appeal. However, the use of products without a dentist supervision, whether for an exaggerated time or a very high concentration, can cause damage to both the dental structure and the oral microbiota, causing imbalance capable of favoring the installation of pathologies. By a randomized controlled doubleblind clinical trial, thirty-nine volunteers were divided into three groups: 10% carbamide peroxide, 4% hydrogen peroxide, and placebo, to evaluate whether home tooth bleaching with these products causes any change in the oral microbiota, and in addition, to verify the presence of dental sensitivity and the color change, comparing the groups. The products were applied according to the manufacturer's recommendations on both arcades by custom-made trays for 21 days. Dental biofilm samples were collected in five moments: before bleaching, after 21 days of use and 7, 14 and 28 days after the end of treatment. These samples were cultivated in specific media for the isolation and quantification of Streptococcus mutans, Lactobacillus spp. and Candida spp. Dental shade and sensitivity were checked weekly during the survey.One-way ANOVA and non-parametric Kruskal-Wallis test were used to compare the initial characteristics and the Bonferroni post-hoc test was used to identify the differences. The results indicated that there was no statistically significant difference in action between the two bleaching agents studied. Both 10% carbamide peroxide and 4% hydrogen peroxide were effective, bleaching the teeth even after suspension of use, caused mild and transient tooth sensitivity, which was not verified after 7 days without application and at the concentrations used, only Lactobacillus presented a significant reduction during the use of bleaching agents, returning to normal levels after 7 days without use.